2020
DOI: 10.24189/ncr.2020.055
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of medium to large mammals in Samunsam Wildlife Sanctuary, Sarawak in relation to the newly constructed Pan-Borneo Highway

Abstract: Protected Areas in Borneo retain some of the best examples of biodiversity and are the last refuge for wildlife conservation in tropical rainforests. Therefore, understanding the species richness and composition in increasingly fragmented Protected Areas are crucial in wildlife monitoring and management. The recent road construction splitting the oldest wildlife sanctuary in Sarawak has warranted further investigation on the species distribution. Camera trap survey in Samunsam Wildlife Sanctuary (SWS), western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…The chemical soil properties of the different L-UCH classes are presented in Table 3 . The results were similar to values reported in other studies carried out in Ecuador and Latin America (e.g., [ 7 , 8 , 30 ]). However, soil pH at the different L-UCH showed significant statistical differences (HSD Tukey), in which SDF, OCA, and CoAS had a soil pH over 6.0, whereas for GLd and CyAS the soil pH was close to 5.0.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The chemical soil properties of the different L-UCH classes are presented in Table 3 . The results were similar to values reported in other studies carried out in Ecuador and Latin America (e.g., [ 7 , 8 , 30 ]). However, soil pH at the different L-UCH showed significant statistical differences (HSD Tukey), in which SDF, OCA, and CoAS had a soil pH over 6.0, whereas for GLd and CyAS the soil pH was close to 5.0.…”
Section: Resultssupporting
confidence: 92%
“…The main cause of L-UCH is the economic activity of the population, such as timber extraction, or the conversion of forests into agricultural land, together with the ensuring infrastructure construction [ 6 ]. Once the natural vegetation cover is converted, exotic species (plants and animals) are introduced into the disturbed areas, which generally do not have native predators [ 7 ], and, therefore, can provoke additional changes in the ecosystems [ 8 , 9 ]. This exemplifies that human impacts on natural ecosystems can sometimes be irreversible; however, alterations in local environmental and climate conditions are generally observed [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the helminth species diversity in myomorph rodents showed that the helminth fauna of M. arvalis, M. subterraneus and S. uralensis is more diverse, despite the fact that A. agrarius (12 species) and C. glareolus (14) have a greater number of helminth species. The Shannon index values are lower in these rodent species due to the high abundance and dominance of Syphacia nematodes in their helminth fauna (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The study of helminths of wild mammals in protected areas is of particular interest, because, the species diversity of both animal hosts and their parasites is most fully preserved here as a result of the special regime. In the context of global anthropogenic transformations of natural ecosystems, only protected areas are the most favorable places for animals to live in [11][12][13][14][15], the purpose of which is to preserve the biodiversity of forest ecosystems [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the Amazon basin, CH-LUs are mainly driven by illegal logging, the expansion of agricultural activities, the use of uncontrolled fire for the conversion of natural forests into pastures and crop areas (Armenteras et al, 2019), road construction (Perazzoni et al, 2020) as well as due to the protection of livestock (Bos taurus) and other domestic animals from predators (de Lima et al, 2020). These activities cause disturbances in natural forests and protected areas that can lead to the collapse of these ecosystems (Mohd-Azlan et al, 2020). South America has one of the highest average erosion rates (3.53 Mg ha -1 year -1 ) compared to other regions such as Africa (3.51 Mg ha -1 year -1 ) and Asia (3.47 Mg ha -1 year -1 ) (Borrelli et al, 2017).…”
Section: Introductionmentioning
confidence: 99%